Modeling pneumococcal nasopharyngeal acquisition as a function of anticapsular serum antibody concentrations after pneumococcal conjugate vaccine administration. Issue 36 (5th August 2016) - Dagan, Ron; Juergens, Christine; Trammel, James; Patterson, Scott; Greenberg, David; Givon-Lavi, Noga; Porat, Nurith; Gruber, William C.; Scott, Daniel A.
Highlights: High IgG levels after PCVs have a substantial effect on nasopharyngeal carriage. Ethnicity did not influence this association despite differences in carriage rates. These results may have important implications for herd protection. IgG levels higher than defined by WHO for IPD are required to prevent carriage. IgG levels required to protect against acquisition differ between serotypes. Abstract: Background: A prior 7- and 13-valent pneumococcal conjugate vaccine (PCV7 and PCV13) study provided sufficient data ( N = 1754; Jewish, n = 1154; Bedouin, n = 595; other, n = 5) to investigate the association between nasopharyngeal (NP) acquisition of common PCV7 serotypes and cross-reacting 6A (PCV7 + 6A) and IgG concentrations. Methods: Using a logistic regression model, serotype specific association between postinfant series IgG concentration (age 7 months) and new NP acquisition between ages 7 and 24 months was assessed and adjusted for ethnicity. From a subset of subjects with new NP acquisition ( n = 9–152 across serotypes studied), new acquisition percentiles and associated IgG concentrations were calculated. Results: For the serotypes studied, new NP acquisition rates decreased as IgG concentrations increased. Ethnicity did not influence these associations despite differences in carriage rates. From the subset with new acquisitions, 50% of the events occurred at IgG concentrations >0.61–5.58 μg/mL; and 10% of the acquisitions occurred at IgG concentrations >2.48–17.69 μg/mL. Conclusion: Remarkably high IgG concentrations are required to reduce NP acquisition. These IgG concentrations differ between serotypes. Ethnicity did not influence the association between high IgG concentrations and prevention of carriage despite differences in carriage rates. Since carriage determines transmission, these results may have important implications for herd protection. Trial registration: ClinicalTrials.gov number, NCT00508742 ;http://clinicaltrials.gov/ct2/show/NCT00508742